Optimizing banana production in aroma Lumajang business using goal programming method and sensitivity analysis - Bramastary, Aurelly Meidy; Kharis, Selly Anastassia Amellia (Jurusan Matematika FMIPA Universitas Jember, 2024)
Lumajang regency, located in the East Java Province, Indonesia, is renowned for its extensive banana cultivation. Aroma Business, situated in Kalibendo Village, Pasirian District, Lumajang Regency, specializes in banana processing. The company faces challenges including suboptimal production levels, underutilization of resources, raw material shortages, and escalating production costs. These issues contribute to financial instability and unmet market demand. This study aims to establish optimal production planning strategies to address these critical challenges. The research employs the Goal Programming method, which is selected for its suitability in addressing multi-objective problems. Optimization of production is essential for achieving desirable outcomes, ensuring both quantity and quality of products. Research conducted with the aid of LINDO software reveals that production costs can be reduced from IDR 6,647,400 to IDR 6,417,000. Additionally, raw material availability can be increased by 1,512 pieces and the production of banana stem chips can be increased from 240 pieces to 372 pieces, resulting in an increase in company profits from IDR 10,506,000 to IDR 11,727,000. Sensitivity analysis indicates that variations in the right-hand side ranges value do not impact the obtained optimal results. Keywords: Banana production, goal programming, optimization, sensitivity analysis, LINDO software. MSC2020: 90B30.